Insights About the Mechanism of the Formation of Supramolecular π‐Stacked Rectangles Based on CuI Bimetallic Complexes Bearing a Bridging Phosphane Ligand. Issue 10 (15th November 2013) - Nohra, Brigitte; Reau, Regis; Lescop, Christophe
Abstract: The variation in the ratio of the reactants in the supramolecular self‐assembly reaction of the bimetallic Cu I "U‐shaped" molecular clip1 with the 1, 4‐dicyanobenzene3 and the 1, 8‐anthracene‐9, 10‐carbonitrile4 "short" ditopic ligand have allowed the observation of new "open" supramolecular assemblies7 and8, respectively, in addition to the previously characterized π‐stacked supramolecular rectangles5 and6, respectively. These new derivatives have been characterized by their solid‐state structure obtained by X‐ray diffraction on single crystals and by NMR spectroscopy in the case of derivative7 . Depending on the extent of the π system included in the core of the homoditopic linker, different behaviors are observed. In the case of derivative7 based on the "phenyl" linker3, a 1:11 /3 ratio affords the open derivative in a good yield, whereas a 1:0.51 /4 ratio allows the isolation of derivative8 in very low yield. These results allow for a tentative analysis of the mechanism that occurs along with the supramolecular self‐assembly processes to afford π‐stacked supramolecular rectangles. Abstract : Variation of the ratio of the reactants in the reaction of a Cu I dimer acting as a "U‐shaped" molecular clip with selected homoditopic π‐conjugated linkers allows the observation of "open" tetrametallic supramolecular assemblies together with π‐stacked metallocyclophanes. This will help us understand the mechanism of such self‐assembly reactions.